(3cJGH aj GdMQha hGdChbGas
(3ChdgG (B:s
(3GYde Cf TQGFW GdETJZGd HgPg Gdafhf CeG GdEeGe GdQGRi abO GNJHGQ efgG eGgh CMSfgG s
(3BNQgG (B:s
(3hGYde Cf gPg GdbQjMI dhbhGFgG Ydi eG Ndbg Gddg MUd GdebUhO SQjYkG EPG ESJYedg ceG PcQfG GdMQGQI ai GdMQGQI hGdHQhOI ai GdHQhOg MUd GdebUhO HEPf Gddg JYGdi JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JTJed Ydi OhGFQ hLOGhd hCTcGd eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs